2012
DOI: 10.3168/jds.2011-4921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of presynchronization and length of proestrus on fertility of grazing dairy cows subjected to a 5-day timed artificial insemination protocol

Abstract: 2016-10-17T18:53:41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 23 publications
1
47
3
Order By: Relevance
“…There are several compelling findings that associate lower conception rates in cows with reduced proestrus duration: Dadarwal et al (2013) found that cows with proestrus of 12 and 36 h had conception rates of 11 and 46% respectively. Ribeiro et al (2012) found a similar trend of lower conceptions rates in cows with shorter proestrous period. Although not consistent among various studies, smaller follicles and low E 2 contents in cows with short proestrus have, in themselves, been the probable reasons for reproduction failure.…”
Section: Proestrous Periodsupporting
confidence: 63%
“…There are several compelling findings that associate lower conception rates in cows with reduced proestrus duration: Dadarwal et al (2013) found that cows with proestrus of 12 and 36 h had conception rates of 11 and 46% respectively. Ribeiro et al (2012) found a similar trend of lower conceptions rates in cows with shorter proestrous period. Although not consistent among various studies, smaller follicles and low E 2 contents in cows with short proestrus have, in themselves, been the probable reasons for reproduction failure.…”
Section: Proestrous Periodsupporting
confidence: 63%
“…A second and larger study in three high-producing herds demonstrated that the double Ovsynch increased P/AI from 38.2% to 46.3% compared with the Presynch-Ovsynch (Herlihy et al, 2012). Finally, a large study involving three seasonally pasture-based milk production herds resulted in similar fertility responses when cows were subjected to the double Ovsynch compared with the Presynch-Ovsynch (Ribeiro et al, 2012b). Therefore, if the choice is to subject all cows to timed AI, or if herds have a high prevalence of anovular cows, the programme of choice should be the double Ovsynch protocol for the first postpartum insemination.…”
Section: Optimising Timed Ai Programmesmentioning
confidence: 88%
“…Ovulation to the first injection of GnRH improves synchronisation of the oestrus cycle and reduces the period of follicular dominance, both associated with greater P/AI (Vasconcelos et al, 1999; Bleach et al, 2004;Santos et al, 2010a). Complete CL demise following treatment with PGF 2α and the timing of the final GnRH are also critical to expose cows to an adequate period of proestrus (Ribeiro et al, 2012b), which controls priming of the uterus for the establishment of pregnancy and the final stages of follicle maturation. Finally, fertility is modulated by the interval between induction of ovulation with the second GnRH and AI (Pursley et al, 1997), as it determines the window during which oocyte and sperm cells are viable for fertilisation (Saacke, 2008).…”
Section: The Ovsynch Protocolmentioning
confidence: 99%
See 2 more Smart Citations